Housing market: the concept, features, and role in the socio-economic development of the state (Nexo Revista Científica, 2021)
The research is based on the dialectical method which predetermines the study of phenomena in their constant development and interrelation. Besides, the article uses a systematic approach, methods of comparative, statistical, and graphical analysis. The novelty of the present article lies in the proposal for adjustments to the calculation of the housing affordability index in the Russian Federation (RF), as well as the proposed typology of housing in the RF taking into account lifestyles of various categories of the population. The authors have developed the version of the content of the infrastructure of the commercial rental of housing, which defines it as a system of material and information conditions ensuring stable and efficient production of housing services (housing rental services) through the operation of both commercial apartment buildings and other objects of the rental housing market. A system of measures is proposed to remove the rental housing market from the shadow and its further development including that of the commercial apartment building business.